Exclusive breastfeeding in a context of intimate partner violence in Brazil (Research, Society and Development, 2022)
The study aim was to identify the experience of exclusive breastfeeding and its relationship with the situation of intimate partner violence from a qualitative approach. The study was carried out in a maternity hospital located in Brazil. The participants were 21 puerperal women, who were in a situation of intimate partner violence in the puerperium and who had at least 180 days postpartum. The quantitative data (the women's sociodemographic, economic, family, and obstetric status) were used for describing the participants. Whereas, the qualitative data were collected through an open interview and recorded in a single moment, they reflected on the experience of breastfeeding in situations of violence by their intimate partners. The qualitative data was treated using the Method of Sense Interpretation; and Male Domination and Symbolic Power, by Pierre Bourdieu, were the theoretical frameworks chosen to discuss the concept of gender in social relationships. Most of the participants were young, black/brown-skinned, had a mean of 10 years of study, all suffered some type of violence by their partners during postpartum, and only one woman followed exclusive breastfeeding until six months. The central category, entitled: “Intimate partner violence and its repercussions on the experience of exclusive breastfeeding”, identified that intimate partner violence impacted in maintaining exclusive breastfeeding, interruption of latching, in addition to affecting the relationship between mother and child. The originality of the theme must be discussed in the academic, practical, governmental, and research spheres in order to strengthen the notification and confrontation of violence and to advocate for exclusive breastfeeding even in adverse contexts.